2013
DOI: 10.1074/jbc.m112.394130
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mutant K-Ras-dependent Phenotypes Using a Panel of Isogenic Cell Lines

Abstract: Background: Many studies analyzing K-Ras function rely on overexpression. Results: Knock-out and knock-in of endogenous mutant K-ras have modest effects on downstream signaling but strong effects on gene expression and transformation. Conclusion: Genomic manipulation allows physiological determination of WT and mutant K-Ras consequences. Significance: Gene expression patterns can be used to monitor inhibition of mutant K-Ras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 43 publications
14
60
0
Order By: Relevance
“…Changes in the expression of IP 3 Rs in cancer cells have been reported previously. Most notably, an increase in IP 3 R3 expression at the mRNA level has been detected in a recent microarray analysis of K-Ras-deleted cells lines (Vartanian et al, 2013). In gastric cancer cells, an increase in IP 3 R3 was observed in the ascites, but not in cancer cells established from primary tumours.…”
Section: Discussionmentioning
confidence: 89%
“…Changes in the expression of IP 3 Rs in cancer cells have been reported previously. Most notably, an increase in IP 3 R3 expression at the mRNA level has been detected in a recent microarray analysis of K-Ras-deleted cells lines (Vartanian et al, 2013). In gastric cancer cells, an increase in IP 3 R3 was observed in the ascites, but not in cancer cells established from primary tumours.…”
Section: Discussionmentioning
confidence: 89%
“…KRAS mutation with concominant loss of the wild-type KRAS allele has also been described in human early T-cell progenitor T-ALL (5). Wild-type RAS may have both tumor suppressive (29,30) and tumor promoting properties (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of growth inhibition in some lines, we found that ARS-853 effectively inhibited RAF-RBD KRAS dependence is well established to be more pronounced in 3-D and/or anchorage-independent settings than in adherent growth assays (10)(11)(12). In line with gene-targeted approaches (10)(11)(12), all tested KRAS G12C cell lines were robustly inhibited by ARS-853 in soft-agar colony formation assays with an average ∼ 2 μ mol/L IC 50 ( Fig. 4C and D ).…”
Section: G12smentioning
confidence: 92%